Research on Architecture of LEO Satellite Internet of Things and Key Technologies - Xiaojin DING; Tao HONG; Rui LIU; Wentao PENG; Gengxin ZHANG (天地一体化信息网络)
First, we analyzed the composition and demand characteristics of LEO satellite IoTs, and designed an architecture of LEO satellite IoTs.Second, to extracted characteristics of electromagnetic environment and channel, we studied electromagnetic environment and channel sensing methods through constructing neural network model.Then, we investigated an active terminal-identifi cation method for detecting active terminals.Finally, considered multiple-input multiple-output as the main approach to improved the capacity of terrestrial mobile communication systems, we explored a pair of algorithms of mining satellite spatial resources for realizing the collision mitigation and capacity improvement of LEO IoT terminals.Simulation results showed that the designed method sofmining spatial-domain resources could mitigated eff ectively signal collisions among IoT terminals, and improved signifi cantly the concurrent accessing number of LEO satellite IoT terminals.